A Flexible Solid Electrolyte with Multilayer Structure for Sodium Metal Batteries. Issue 9 (31st January 2020) - Ling, Wei; Fu, Na; Yue, Junpei; Zeng, Xian‐Xiang; Ma, Qiang; Deng, Qi; Xiao, Yao; Wan, Li‐Jun; Guo, Yu‐Guo; Wu, Xiong‐Wei
Abstract: Solid electrolytes (SEs) can potentially address the inherent safety problems of conventional organic liquid electrolytes. However, their low ionic conductivity and large interfacial resistance limit the practical applications of SEs. Here, a flexible solid electrolyte with a multilayer structure is fabricated by the UV curing of an interpenetrating network of poly(ether‐acrylate) (ipn‐PEA) in the Na3 Zr2 Si2 PO12 /poly(vinylidene fluoride‐hexafluoropropylene) porous skeleton (NZSP/PVDF‐HFP), exhibiting a high Na + transference number of 0.63 and a suitable ionic conductivity of above 10 −4 S cm −1 at 60 °C. In addition, due to the unique structure of the internal rigidity and external flexibility, the composite solid electrolyte can effectively mitigate interfacial ion transfer issues while guaranteeing a certain mechanical strength, and largely inhibiting the formation of dendrite and dead sodium. The solid sodium metal batteries using Na3 V2 (PO4 )3 (NVP) as a cathode possess a discharge capacity of 85 mA h g −1 after 100 cycles at 0.5 C, and achieve above 90% of capacity retention rate during 100 cycles at 0.1 C for Na2/3 Ni1/3 Mn1/3 Ti1/3 O2 (NTMO) at 60 °C. The flexible solid electrolyte with multilayer structure shows a great advantage for managing the ionic conductivity and interface resistance problem, suggesting a promise as a practical sodium metal battery. Abstract : A flexible composite electrolyte with a sandwich structure (CESS) is fabricated by the UV curing of poly(ether‐acrylate) (ipn‐PEA) in a Na3 Zr2 Si2 PO12 /poly(vinylidene fluoride‐hexafluoropropylene) porous skeleton (NZSP/PVDF‐HFP). The internal rigidity and external flexibility of the CESS multilayer structure can effectively mitigate interfacial ion transfer issues while conferring a degree of mechanical strength, as such it shows tremendous application potential for sodium metal batteries.